Islamic banks' contribution to Indonesia districts' economic growth and poverty alleviation - Junaidi Junaidi (Journal of Economics, Finance and Administrative Science, 2024)
Purpose - This research investigates the Islamic banks' intermediation role (e.g. branches and deposits) in financing. It also examines how financing contributes to the regions' economic growth and poverty alleviation as a predictor and mediator variable. Design/methodology/approach A total of 297 observations were extracted from 33 Indonesian districts and 14 Islamic banks during the period 2012-2020. Fixed-effect regression analysis was used to examine variable's interactions. Findings The empirical results indicate that Islamic banks have adopted a channelling role towards redistributing capital from lender to borrower. Besides, there are crucial roles in developing economies and reducing poverty at the district level. This study also reinforces the critical role of financing in mediating the relationship between branches and deposits as predictor variables and GDP and poverty as outcome variables. Research limitations/implications The current study was limited to Indonesian Islamic banks and the district's perspective. Future research needs to cover sub-districts and other poverty measurements (e.g. human education and development perspectives), including conventional and Islamic banks. It can help practitioners, regulators and researchers observe the dynamic behaviour of the banking sector to understand its role in the economic and social fields. Practical implications Bank managers and regulators should promote branches, deposits and financing. It also enlightens people about the essential role of Islamic banks and their fundamental operations in business and economics. Originality/value This study contributes to economic literature, bank managers and local governments' decision-making processes by developing and testing an economic growth and poverty model.
Keywords: A13; G21; O4; 330; Deposits; Economic growth; Financing; Islamic bank branches; Poverty reduction